Informal networked learning; a network in the wild - Haxell, Ailsa (Proceedings of the International Conference on Networked Learning, 2012)
Shifting work predicated on talking to the very small screen of mobile phones, a space approximately 3cm square, with a 160 characters imposition on each utterance, and where no-one gets seen or heard, generates a significant challenge. This challenge is faced by Youthline, New Zealand, a youth oriented telephone helpline. There is no evidence-base for such a practice; there never is for new practice. How then is new practice learned? One of the teaching and learning challenges that becomes apparent is that something cannot be taught until it is known, and in not knowing how the practice would develop there could be little preparation for those involved. They had to learn from each other. What evolves provides a unique opportunity for studying an informal networked learning, a network in the wild. This paper draws on conceptual and analytical tools of actor-network theory (ANT). In tracing the detailed activities of those involved it becomes possible to see practice might have been, and still could be otherwise. The networked learning that occurs is a reflection of the interactions between those involved. In working the technology to suit human needs, it becomes apparent the technology simultaneously shapes those involved. The technology in this network is demonstrably not a passive carrier of conversation, nor are young people making use of the service passive recipients, the counsellors do not move in untroubled ways from one medium to another, and counselling does not remain the same. In observing practice development it becomes evident that things happen due to contingent relationships rather than individually held agency. Recognizing agency as distributed disrupts conceptions of who leads, who follows, of who teaches or learns, and who gets to define whom. An attribution error is made when agency is located individually; young people are cast as choosing text for pathological reasons that spans being developmentally challenged through to being members of a thumb generation. Such errors creating barriers to empowerment are challenged by the new configurations that occur. Studying networks in the wild brings to the fore concerns associated with what is mainstream or not. What is seen as different, edgy, acceptable or unacceptable, desirable or abhorrent depend on the vantage point one has. Looking at networks in the wild provides a further vantage point. There is potential that other educators might learn from network learning spaces where the borders on innovation and of literacy practices are less firm.